Analisis Pelestarian Warisan Budaya Cina Benteng Melalui Museum Benteng Heritage Kota Tangerang - Clarista Pundarika; Roozana Maria Ritonga (JURNAL MANAJEMEN PENDIDIKAN, 2026)
ANALYSIS OF CINA BENTENG CULTURAL HERITAGE PRESERVATION THROUGH MUSEUM BENTENG HERITAGE TANGERANG CITY Beneath the rapid development of Tangerang City lies a cultural heritage on the verge of being forgotten: the identity of the Cina Benteng community, a Chinese Peranakan group that has acculturated with local society since the 17th century. Museum Benteng Heritage stands as the first Chinese Peranakan museum in Indonesia, located in the Pasar Lama area, serving as one of the last bastions for the survival of this culture. This study aims to analyze the cultural heritage preservation efforts undertaken by Museum Benteng Heritage, while identifying the challenges faced and their respective mitigation strategies. This study employs a descriptive qualitative approach, with data collected through semi-structured interviews, direct observation, and documentation. Informants include the museum founder, Cina Benteng cultural experts, museum guides, and tourists selected through purposive sampling, with data validity tested via source triangulation. The results indicate that Museum Benteng Heritage actively and comprehensively implements cultural preservation, encompassing the physical conservation of historic heritage buildings, artifact collection management as a living cultural documentation center, historical narrative presentation through interactive tours, community-engaged cultural programs, and the utilization of digital technology as an educational medium. Conversely, the museum faces real challenges, including area conditions that do not fully support cultural tourism comfort, low awareness among some local community members, limited promotional reach to the younger generation, and managerial dependence on a single individual. This study confirms that museums are living spaces continuously striving to pass down cultural identity. Its sustainability requires genuine collaboration between museum management, local government, cultural communities, and society.